A imagem de língua portuguesa no discurso de professores e alunos do Ensino Fundamental e Médio : a perspectiva do ensino - (e)aprendizagem - Silva, Juliana Orsini da (2007)
In this work, we preceded the analysis of the teachers' speech and students on the Portuguese language based in the theoretical presuppositions of the Analysis of Speech of French line. The subject that orientated this work was: which senses produced on Portuguese language in the teachers' speech and students tends in view the image that they possess of this language starting from the position that they occupy in the school space? For us to answer this subject, we analyzed an extracted corpus of a questionnaire for us organized and applied to the teachers and students from the basic and high school. The research revealed that, in the teachers' speech, there is a language conception that is built ideologically. The senses produced in relation to the uses of the Portuguese language they established your bases in the speech of the educated norm. The language image that she enrolled is of a language while closed system, the imaginary language. We also understood that, through the imaginary linguistic produced, the person that stands back of the imaginary language, of the idealized language, he/she stands back of the condition of being Brazilian, since the language is constituted as a national identity. Besides that, we noticed different position-subjects, in that the teacher let to glimpse the image that they incorporated that that defends the linguistics, but on the other hand, it reproduced the precepts of the traditional teaching, happening on the speeches control procedures and game of images. And for the students, for to 4th grade, the writing shows the image in relation to the discipline, appearing as something that establishes power. In the 8th grade, the students projected in your statements the speech of the traditional grammar as learning/teaching place, of the knowledge. It appeared as effect, the language image correct that, for those students, it is constituted in the domain of the grammatical nomenclatures. This vision was also revealed in the discursive sequences of the 3rd grade. As a consequence of this imaginary of language, we saw that the student's linguistic identity is being built during all your school life. In relation to the importance of the discipline, we observed that, one way or another, to learn Portuguese language, for the students, it is justified with the concern and the care with the correct use of the language as form of power and to be included in the group, be at the school, be out of the school.